Studi Komparatif Tentang Praktik Peralihan Tanah Hibah Ke Pihak Lain (Hukum Islam dan Hukum Positif Indonesia) - Kurniati, Herlina; Mellenia, Reva; Septiana, Evy (Universitas Islam Negeri Raden Intan Lampung, 2022)
Grant could divert to person other through transition right through the grant. Practice transition soil grant to party other this start from practice grant at the beginning where a second split party has die world so that soil grant the fall down to expert inheritance from receiver grant. From party expert inheritance no need soil the so that soil the diverted to others. On moment transition soil grant, deed grant in beginning no found however transition soil grant the permanent conducted, the para party intends to look after deed grant the after did practice transition the more formerly. The Formula's problem in this study is how to practice transition soil grants to party other and review Islamic law and positive law that occurred in Gunung Terang Village. This study is a qualitative and character descriptive normative study carried out on practice transition soil grant to party others that occurred in Gunung Terang Village. The result of the study is the existence of transition grant soil where soil obtained from results gift grant from others then diverted return to others through grant also. The practice of transition soil grant to party other this conducted by oral witnessed by a party related like family and para witness with To do hand over accept grant soil. In a review of Islamic law, practice transition soil grants to party other this already in accordance by Islam because already fulfill get along and condition grant. Meanwhile, positive law is not yet in accordance and not allowed because no existence proof authentic or deed grant moment did practice transition soil grant them. Keywords: Grant, Switch, another party, soil